Tuberculous osteomyelitis of proximal fibula: An unusual presentation of tuberculosis - Jain, Gunjar; Mahmood, Asjad; Nag, Hira Lal; Gupta, Pranav; Gopinathan, Vikram Raj; Yadav, Rajni (Indian Journal of Case Reports, 2021)
Tubercular involvement of the proximal fibula is rare. We present a case of tuberculosis of proximal fibula in an immunocompetent 22-year-old female. She was diagnosed clinically as a case of cellulitis. Radiological investigations, including magnetic resonance imaging revealed a destructive lesion in her right proximal fibula. Finally, by fine-needle aspiration cytology and GeneXpert polymerase chain reaction, a diagnosis of tuberculous osteomyelitis of proximal fibula was established. She was managed non-operatively with multidrug antitubercular chemotherapy. A high index of suspicion is required to make a diagnosis of musculoskeletal tuberculosis of such a rare site in the early stages.